Effects of supernovae feedback and black hole outflows in the evolution of Dwarf Spheroidal Galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Lanfranchi, Gustavo Amaral; Caproni, Anderson; Soares, Jennifer F.; de Oliveira, Larissa S.
Abstract: The gas evolution of a typical Dwarf Spheroidal Galaxy is investigated by means of 3D hydrodynamic simulations, taking into account the feedback of type II and Ia supernovae, the outflow of an Intermediate Massive Black Hole (IMBH) and a static cored dark matter potential. When the IMBH's outflow is simulated in an homogeneous medium a jet structure is created and a small fraction of the gas is pushed away from the galaxy. No jet structure can be seen, however, when the medium is disturbed by supernovae, but gas is still pushed away. In this case, the main driver of the gas removal are the supernovae. The interplay between the stellar feedback and the IMBH's outflow should be taken into account.